2006
DOI: 10.1191/1362168806lr195oa
|View full text |Cite
|
Sign up to set email alerts
|

Formulaic sequences and perceived oral proficiency: putting a Lexical Approach to the test

Abstract: This study reports a small-scale experiment that was set up to estimate the extent to which (i) the use of formulaic sequences (standardized phrases such as collocations and idiomatic expressions) can help learners come across as proficient L2 speakers and (ii) an instructional method that emphasizes ‘noticing’of L2 formulaic sequences can help language learners add such phrases to their linguistic repertoire. Participants were 32 college students majoring in English. Over the course of 22 teaching hours they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
381
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(396 citation statements)
references
References 6 publications
11
381
2
2
Order By: Relevance
“…Implicit in this definition is the fact that, since formulaic sequences are accessed as wholes, they require minimal processing capacity, leading to more fluent speech (Ellis, 2003). Ample evidence lends support to the efficiency of investment in formulaic sequences either as an approach in its own right or as one type of CS (e.g., Boers, Eyckmans, Kappel, Stenger, & Demecheleer, 2006;Canale & Swain, 1980;Ellis, 2005;Howarth, 1998;Thornbury, 2002;Shin & Nation, 2008).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Implicit in this definition is the fact that, since formulaic sequences are accessed as wholes, they require minimal processing capacity, leading to more fluent speech (Ellis, 2003). Ample evidence lends support to the efficiency of investment in formulaic sequences either as an approach in its own right or as one type of CS (e.g., Boers, Eyckmans, Kappel, Stenger, & Demecheleer, 2006;Canale & Swain, 1980;Ellis, 2005;Howarth, 1998;Thornbury, 2002;Shin & Nation, 2008).…”
Section: Treatmentmentioning
confidence: 99%
“…As a first step, the teacher's job is raising learners' awareness of the pervasiveness of formulaic sequences in written or spoken English (Boers et al, 2006), and of their beneficence in language reception and production. Introducing the concept of chunks by bringing up some familiar examples (in the morning, go for a walk, wearing glasses, how much does .…”
Section: Treatmentmentioning
confidence: 99%
“…In this context, particularly good knowledge of idiomatic expressions can help language learners to reach proficiency level in the target language (Boers et al, 2006), and is even generally equated with sounding more natural (Schmitt, 2000;Wray, 1999). Indeed, lack of competence in idiomatic expressions can even result in communication breakdowns (Cooper, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Ellis and Sinclair (1996: 234), '[t]he attainment of fluency, in both native and foreign languages, involves the acquisition of memorized sequences of language'. Boers et al (2006), for example, showed that L2 speakers were judged as more proficient when they used formulaic sequences.…”
Section: Spoken Fluency C2mentioning
confidence: 99%